1964
DOI: 10.1542/peds.34.4.542
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Atresia and Tracheoesophageal Fistula

Abstract: The members of the Surgical Section of the American Academy of Pedatrics were surveyed regarding their results in treating patients with esophageal atresia and tracheoesophageal fistula for the five-year period ending January 1, 1963. Information on 1,058 patients was received. The data was processed with the aid of a computer and the results, not easily summarized, have been presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
2

Year Published

1967
1967
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(10 citation statements)
references
References 0 publications
0
6
2
Order By: Relevance
“…Anastomotic leakage into the mediastinum occurs in 14% to 21% of infants who have undergone a surgical EA repair. Leaks result from the small, friable lower segment, ischemia of the esophageal ends, excess anastomotic tension [9], sepsis, poor suturing techniques, type of suture [10, 11], excessive mobilization of the distal pouch [12], and increased gap length [9, 11] To minimize the incidence of anastomosis leak, fibrin glue was tried based on studies of different sites that have indicated that fibrin glue enhances wound healing [13, 14]. In the present series, the overall incidence of anastomotic leak was 26.6%, which is comparable to that of other reported series [7, 8], although in our series we selected only cases where the gap between the two esophageal pouches was ≥ 2 cm (long‐gap cases [10]).…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic leakage into the mediastinum occurs in 14% to 21% of infants who have undergone a surgical EA repair. Leaks result from the small, friable lower segment, ischemia of the esophageal ends, excess anastomotic tension [9], sepsis, poor suturing techniques, type of suture [10, 11], excessive mobilization of the distal pouch [12], and increased gap length [9, 11] To minimize the incidence of anastomosis leak, fibrin glue was tried based on studies of different sites that have indicated that fibrin glue enhances wound healing [13, 14]. In the present series, the overall incidence of anastomotic leak was 26.6%, which is comparable to that of other reported series [7, 8], although in our series we selected only cases where the gap between the two esophageal pouches was ≥ 2 cm (long‐gap cases [10]).…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Congenital BEF is mostly found in childhood and is very rare in adults. 9 There have been reports of BEF due to esophageal tuberculosis, 10 and recently, BEF has been reported in patient with coinfection of severe acute respiratory syndrome coronavirus 2 and tuberculosis. 11 In patients with CD, there have been some cases of BEF due to esophageal involvement, 12 although esophageal involve ment in CD is rare and is reportedly difficult to diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…A neural tube fails to close and causes spina bifida; 1 an esophagus errantly connects into the windpipe and produces esophageal atresia. 3 Since the revolutionary discovery of the structure of DNA by Watson and Crick in 1953, 4 scientists have primarily worked to characterize the biochemical signals that underlie tissue assembly in the embryo. 1 This important work has helped elucidate the vast signaling and gene regulatory networks that pattern the early embryo and drive the differentiation of organspecific cell types.…”
Section: Introductionmentioning
confidence: 99%